Estudio Comparativo de la Efectividad del Tratamiento Restaurador Atraumático con y sin Remoción Químico Mecánica en Dientes Deciduos. - Guillén Borda, Celso (2003)
In order to conduct this study were selected 100 patients from the clinics consult devices of the Odontology School of the UMSM and from the Odontopediathrics Departament of the Instituto Nacional del Niño from to 8 to 10 years old, presence of dental caries in both half dental arcades without any other systemic pathology associated. With the permission of the parents or the personal in charge of the patient, we proceed to fill the odontogram and initiate the Non Traumatic Restoration Treatment (NTRT) according to the protocol: Caries within half dental arcade without chemical-mechanical caries tissue remotion and with standard odontological treatment (group A) and caries within the left half dental arcade with chemical-mechanical caries tissue remotion using CARISOLV according to the manufacturer specifications (group B). The dental final restorations were planned to be perfomed with glass ionomer. We conducted the patients follow up with a clinical evaluation through the observation of the following signs and symptoms: dental pain, edema, fistulae development, soft tissue color changing and dental color changing. These evaluations were performed every 5 months until 15 mouths. Until now, the preliminary conclusions from the first evaluation are: (I) The use of CARISOLV allows health tissue preservation and by these means reduces the risk of pulpar exposition (II) CARISOLV removes entirely the caries lesions as the conventional management, (III) The cavity gets ready for restoration when the dentine became hard; (IV) It. is been observed that CARISOLV only react against the dentine with caries; (V) The visual appearance oft he dental surface treated with CARISOLV shows a color that waves from pale gray to yellow. The use of the NTRT(1,2) employing a chemical-mechanical remove system has a great importance in the daily clinical odontological practice mainly over the oral health promotion programs lowering its costs and gaining efficacy. The anticariogenical properties of the glass ionomer has been proved with the streptoccocus mutans culture colonies reduction in association with cariostatics or dentine softeners as CARISOLV This feature has contributed to a significant improve of the treatment succes ratio.